High‐resolution fjord sediment record of a receding glacier with growing intermediate proglacial lake (Steffen Fjord, Chilean Patagonia). Issue 1 (25th November 2020) - Piret, Loic; Bertrand, Sebastien; Hawkings, Jon; Kylander, Malin E.; Torrejón, Fernando; Amann, Benjamin; Wadham, Jemma
Abstract: Proglacial lakes are effective sediment traps but their impact on the reliability of downstream sediment records to reconstruct glacier variability remains unclear. Here, we investigate the sedimentary signature of the recent recession of Steffen Glacier (Chilean Patagonia, 47°S) in downstream fjord sediments, with a focus on identifying the trapping (decreased downstream sediment yield) and filtering (removal of coarse particles) effectiveness of a growing intermediate proglacial lake. Four sediment cores were collected along a 14 km longitudinal transect in Steffen Fjord and the sediment physical and chemical properties were compared with aerial imagery at high temporal resolution. The caesium‐137 ( 137 Cs) chronology of the most distal core and sediment trap data suggest that sediment accumulation in the fjord remained relatively stable through time, despite the accelerating glacier recession and the growth of Steffen proglacial lake. This is in contrast with many studies that indicate a decrease in sediment yield during proglacial lake expansion. It implies that the increase in sediment export due to accelerating meltwater production may be balanced by the sediment trapping effect of the growing proglacial lake. The fjord sediments show a slight fining upward accompanied by a marked decrease in flood‐induced grain‐size peaks, most likely due to the increasing filtering and dampening effect of the expanding proglacial lake. Our findings show that the filtering effect of the proglacial lake reached a threshold in 1985, when the lake attained an area of 2.02 km 2 . The additional 5 km of glacier recession during the following 32 years did not have any significant impact on downstream sedimentation. This study confirms that proglacial lakes act as sediment traps but it indicates that (1) the trapping effect can be outpaced by accelerating glacier recession and (2) the filtering effect becomes stable once the lake attains a certain critical size. © 2020 John Wiley & Sons, Ltd. Abstract : Fjord sediments are one of the best high‐resolution archives of glacier variability. Our results show that growing intermediate proglacial lakes result in a progressive decrease in downstream sediment grain size until the lake area reaches a threshold. In parallel, sediment retention in such a lake increases but it can be compensated by accelerating glacier shrinkage, resulting in stable sedimentation rates in the fjord downstream.